Artificial intelligence : an illustrated history : from medieval robots to neural networks - Pickover, Clifford A. (Sterling illustrated histories., 2019)
"From medieval robots and Boolean algebra to facial recognition, artificial neural networks, and adversarial patches, this fascinating history takes readers on a vast tour through the world of artificial intelligence. Award-winning author Clifford A. Pickover (The Math Book, The Physics Book, Death & the Afterlife) explores the historic and current applications of AI in such diverse fields as computing, medicine, popular culture, mythology, and philosophy, and considers the enduring threat to humanity should AI grow out of control. Across 100 illustrated entries, Pickover provides an entertaining and informative look into when artificial intelligence began, how it developed, where it's going, and what it means for the future of human-machine interaction."